2007
DOI: 10.1175/jcli4023.1
|View full text |Cite
|
Sign up to set email alerts
|

Global Distribution of Tropical Deep Convection: Different Perspectives from TRMM Infrared and Radar Data

Abstract: Cold cloud features (CCFs) are defined by grouping six full years of Tropical Rainfall Measuring Mission (TRMM) infrared pixels with brightness temperature at 10.8-m wavelength (T B11 ) less than or equal to 210 and 235 K. Then the precipitation radar (PR)-observed precipitation area and reflectivity profiles inside CCFs are summarized and compared with the area and minimum temperature of the CCFs. Comparing the radar with the infrared data, significant regional differences are found, quantified, and used to d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

27
198
2

Year Published

2009
2009
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 222 publications
(227 citation statements)
references
References 38 publications
27
198
2
Order By: Relevance
“…A majority of the DCCs analyzed are located in the lower latitudes and are associated with the Intertropical Convergence Zone. The locations of more frequent DCCs align well with what is shown in Liu et al [2007], although it should be noted that cloud fraction is not the variable shown here.…”
Section: Methodssupporting
confidence: 86%
“…A majority of the DCCs analyzed are located in the lower latitudes and are associated with the Intertropical Convergence Zone. The locations of more frequent DCCs align well with what is shown in Liu et al [2007], although it should be noted that cloud fraction is not the variable shown here.…”
Section: Methodssupporting
confidence: 86%
“…Radar and/or microwave measurements (e.g. Alcala and Dessler, 2002;Liu and Zipser, 2005;Houze Jr. et al, 2007;Liu et al, 2007;Hong et al, 2008) certainly add a new dimension to the remote sensing of convective systems, however the emphasis should be on the synthesis of measurements made at different spectral ranges and the synergistic use of them to exploit their strengths in improving our understanding of cloudprecipitation interactions.…”
Section: Discussionmentioning
confidence: 99%
“…A large-scale diurnal model of the Asian monsoon was also studied by TRMM data (Krishnamurti and Kisthwal 2000). At a much finer spatial scale, the TRMM PR data were used to study the characteristics and life cycle of the monsoon convection and rain in the northern Indian subcontinent and part of the Himalayas (Bhatt and Nakamura 2005;Houze et al 2007;Liu et al 2007). The hydrologic cycle for the tropics was also studied by TRMM data (Roads 2003).…”
Section: Introductionmentioning
confidence: 99%